SELF-DISCIPLINE IS ESSENTIAL TO OVERCOME DIABETES COMPLICATIONS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUBANG KERIAN, KELANTAN, 16 June 2016 The number of people with diabetes in Malaysia has now reached 1.2 million, with 650,000 new cases recorded every year and with most of them being unaware of having the chronic disease until it has spread and affecting their quality of life.